Supercapacitor performance with activated carbon and graphene nanoplatelets composite electrodes, and insights from the equivalent circuit model - Ab Rahim, Abdul Hakim; Ramli, Nabilah; Nordin, Anis Nurashikin; Abd Wahab, Mohd Firdaus (Elsevier, 2021)
Graphene is the preferred material for supercapacitor electrodes in comparison to the conventional acti- vated carbon (AC). However, there are trade-offs between the usage of these two materials. Further un- derstanding of each material’s contribution is needed, especially when they are combined as a composite electrode. This work explores the properties of AC, Graphene Nanoplatelet (GNP), and their composite when they are utilized as supercapacitor electrodes. The characteristics of AC and GNP materials were first reported separately, followed by reports on the supercapacitor performance of pure AC electrodes, pure GNP electrodes, and composite electrodes (AC + GNP). Electrochemical characterization was con- ducted where the specific capacitance, equivalent series resistance, and self-discharge of the prototypes were analyzed. It was found that the specific capacitance of the supercapacitor can be linearly improved by ∼5% with the addition of 20 wt% GNP. However, the self-discharge result indicated a contradictory per- formance, where the GNP prototypes with higher wt% lost 2% more charge due to the ohmic conductivity of the materials. This work proposes an equivalent circuit model (ECM), which was developed and sim- ulated to reflect the behavior of the prototypes during self-discharge. The model successfully mimicked the charging and open-cell voltage procedure with less than 0.2% error for all prototypes. The model was used to explain AC and GNP’s charging mechanism in relation to the electrode-electrolyte interface layers where the addition of GNP was found to facilitate better penetration of the ions into the Helmholtz sur- face layer compared to the pure AC electrode. The ECM also revealed that mesopores play a more critical role in charge storing compared to micropores, especially in fast charging procedures.